(untitled) (Actual Problems of Psychology in Educational Institutions, 2018)
The article is devoted to the analysis of the problem of sustainable development as the basis of the meaningful life choice of a person in the unstable conditions of socio-cultural reformation of civilization. It is emphasized that education is an integral part of the universal phenomenon of development, the main priority of sustainable development of society. The author emphasizes that the application of the integrative (centrist) model of sustainable development allows to expand the scope of education, to fill it with a personal meaning. In the plane of the above, the peculiarities of the development of the cognitive thinking style of pupils of teenage ages are analyzed. The conclusion is made on the necessity of purposeful escort of this process in the conditions of sustainable development education.